Submarginal debris transport and till formation in active temperate glacier systems: The southeast Iceland type locality. (1st September 2018) - Evans, David J.A.; Roberts, David H.; Hiemstra, John F.; Nye, Kathryn M.; Wright, Hanna; Steer, Andrew
Abstract: Exhaustive sedimentological analysis of freshly exposed subglacial surfaces and moraines in southern Iceland provides diagnostic sedimentological signatures of: a) debris transport pathways through active temperate glacier snouts; and b) till production in subglacial traction zones dominated by deforming layers. Three till end members are recognised based on stratigraphic architecture: 1) thin and patchy tills over eroded bedrock; 2) single push moraines and complexes; and 3) overridden moraines or outwash fans. Typical till thicknesses are 0.10–1.40 m, with each till relating to a deformation event driven by the seasonally tuned processes of glacier sub-marginal shearing, freeze-on, squeezing and bulldozing. Clast form trends demonstrate progressive modification towards mature forms in subglacial traction zones with till being clearly differentiated from scree and glacifluvial deposits. Clast macrofabric strengths are variable, rarely matching those of laboratory shearing experiments, except where obviously lodged clasts are abundant. They also consistently record former glacier flow directions. But localized variability is introduced by bedrock protuberances, cavity infill, clast interference and freshly imported plucked clasts. Within tills, macrofabrics strengthen from lower (B horizon) to upper (A horizon) tills but at the outer edges of sub-marginally thickening till wedges or push moraines, seasonally-driven cycles of squeezing/flowage, freeze-on/melt-out and bulldozing give rise to a range of clast macrofabric strengths as well as superimposed deformation signatures. This reflects two extremes of till emplacement including the more mobile, flowing and often liquefied matrixes in push/squeeze moraines and, in contrast, the lodgement, deformation and ploughing at the thin end of sub-marginal till wedges. Highlights: Diagnostic sedimentological signatures defined for subglacial traction till. Three till end members recognized based upon stratigraphic architecture. Single till thickness including combined A and B horizons is only 0.10–1.40 m. Clast forms show progressive modification to maturity in subglacial traction zone. Macrofabric strengths are variable but increased by greater lodged clast proportions.